Advertisement Remove all ads

Solve the Following Quadratic Equations by Factorization: A2x2 - 3abx + 2b2 = 0 - Mathematics

Solve the following quadratic equations by factorization:

a2x2 - 3abx + 2b2 = 0

Advertisement Remove all ads

Solution

a2x2 - 3abx + 2b2 = 0

⇒ a2x2 - 2abx - abx + 2b2 = 0

⇒ ax(ax - 2b) - b(ax - 2b) = 0

⇒ (ax - b)(ax - 2b) = 0

Therefore,

ax - b = 0

ax = b

x = b/a

or,

ax - 2b = 0

ax = 2b

x = 2b/a

Hence, x = b/a or x = 2b/a

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

RD Sharma Class 10 Maths
Chapter 4 Quadratic Equations
Exercise 4.3 | Q 16 | Page 19
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×